Dukungan Organisasi yang Dirasakan: Anteseden, Proses, dan Hasil - Ignatius Soni Kurniawan; Mugi Harsono (IPB University, 2021)
As an organizational asset, employees have an important role in the success of the organization. How to bring up employees who feel supported by the organization and follow the norms of reciprocity with a feeling of obligation to make positive efforts for the organization is the aim of the discussion in this article. The contribution of the article arises from the urgency to provide an explanation of the mechanism that underlies the theory of Perceived Organization Support (POS) for novice researchers in linking the antecedents and consequences of POS. The managerial implication leads to the role of the manager to start by first showing support to his employees in order to move the norm of individual reciprocity to be able to enjoy the utility of POS which includes direct benefits for the welfare of individuals and organizations. Variations of POS measurement items are also discussed to provide recommendations for instrument choice among alternatives. Future POS researchers can take a look at trends in POS-related businesses such as worker collaboration, changes in individual-organizational relationships, and across cultures.